2020
DOI: 10.3390/genes11040394
|View full text |Cite
|
Sign up to set email alerts
|

The POU Transcription Factor POU-M2 Regulates Vitellogenin Receptor Gene Expression in the Silkworm, Bombyx mori

Abstract: Vitellogenin receptors (VgRs) play critical roles in egg formation by transporting vitellogenin (Vg) into oocytes in insects. Although the function of VgR in insects is well studied, the transcriptional regulation of this gene is still unclear. Here, we cloned the promoter of the VgR gene from Bombyx mori (BmVgR), and predicted many POU cis-response elements (CREs) in its promoter. Electrophoretic mobility shift and chromatin immunoprecipitation assays showed that the POU transcription factor POU-M2 bound dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In this study, we found that expression of homeodomain transcription factors POU-M2, Antp, and Abd-B was upregulated by 20E, and further demonstrated that these transcription factors were involved in the transcriptional regulation of CLIP13 by directly binding to CREs in its promoter region. Previous studies indicated that insect homeodomain transcription factors played pivotal roles in segment determination, tissue development, cell fate determination of imaginal discs, egg formation, and ecdysteroidogenesis (Lewis, 1978;Bondos et al, 2004;Meng et al, 2015;Shen et al, 2020). Our findings provide new insight into the functions of homeodomain transcription factors in insect molting.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this study, we found that expression of homeodomain transcription factors POU-M2, Antp, and Abd-B was upregulated by 20E, and further demonstrated that these transcription factors were involved in the transcriptional regulation of CLIP13 by directly binding to CREs in its promoter region. Previous studies indicated that insect homeodomain transcription factors played pivotal roles in segment determination, tissue development, cell fate determination of imaginal discs, egg formation, and ecdysteroidogenesis (Lewis, 1978;Bondos et al, 2004;Meng et al, 2015;Shen et al, 2020). Our findings provide new insight into the functions of homeodomain transcription factors in insect molting.…”
Section: Discussionsupporting
confidence: 53%
“…During insect metamorphosis, POU-M2 reportedly interacted with abdominal-A (abd-A) to regulate expression of WCP4 and other WCPs to complete postembryonic development and differentiation of the wing discs (Deng et al, 2011(Deng et al, , 2012. In addition, POU-M2 was shown to play an important role in insect vitellogenesis by directly regulating expression of Vg and VgR (Lin et al, 2017;Shen et al, 2020). In the present study, we found that POU-M2 was involved in transcriptional regulation of CLIP13 in the epidermis.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In Drosophila melanogaster , the POU factor drifter regulates cell proliferation and differentiation of wing imaginal discs [21], the differentiation and migration of tracheal cells and neurons [22,23], and the expression of dopa decarboxylase [24]. In Bombyx mori , the POU factor POU-M1 is involved in the transcription of sericin-1 gene [25], and POU-M2 regulates the expression of fibroin heavy chain (fib-H) [26,27], wing disc cuticle protein 4 (WCP4) [28,29], steroidogenic enzyme phantom [30], vitellogenin (Vg) [31], vitellogenin receptor (VgR) [32], and diapause hormone and pheromone biosynthesis-activating neuropeptide (DH-PBAN) [33]. Also, POU-M2 regulates the expression of DH-PBAN and phosphatase and tensin homologue in Helicoverpa armigera [34,35].…”
Section: Introductionmentioning
confidence: 99%